The challenge of xenophobia for international tourism: A case study of Salzburg - Aschauer, Wolfgang (2012)
Several countries in the European Union are struggling with the consequences of the global financial and economical crises at different levels. One social outcome of the crises seems to be re-nationalization, the renaissance of values, preserving order and denying egalitarianism and tolerance. These developments in Europe can also affect international tourism. Ethnic minorities in the tourism business, as well as tourists from specific countries, may find themselves in a difficult situation because of certain tendencies of (cultural) racism.This article presents a case study of ethnic prejudice in Salzburg and highlights that negative attitudes towards immigrants are prevalent in the Austrian society. Between April and June (2009) inhabitants of the autochthonous population in Salzburg (without migration background) were interviewed (n = 253). The standardized questionnaire measures how the host society assesses the living conditions of foreigners in Salzburg, gives insights about intercultural relations to certain immigrant groups and explores which individual, structural or societal-based factors influence ethnic prejudice. The study shows that the host society interprets the demographic and socioeconomic situation of immigrants quite realistically but they demonstrate a high level of xenophobia towards specific groups.Therefore it has to be concluded that even a city which is familiar with a lot of different cultures due to a high worldwide tourism demand is not free of ethnic prejudices especially towards groups with a higher social distance to the local population (e.g. Muslims). This may also have certain implications for future tourism. Ethnic prejudice may lead to intercultural misunderstandings, problematic host-guest relations and may affect immigrants working in the tourism sector.